Niemiecka dywersja w Polsce w 1939 r. w świetle dokumentów policyjnych i wojskowych II Rzeczypospolitej oraz służb specjalnych III Rzeszy, część 2 (sierpień–wrzesień 1939 r.) - Chinciński, Tomasz (Pamięć i Sprawiedliwość, 2006)
In the second part of this article German diversion in Poland from August to September 1939 was described. The author tries to make reconstruction and analysis of the German diversion organized and realized by intelligence service of Germany at this time. At the end of August 1939, before the beginning of the Second World War, German diversionist agents reported to Reinhard Heydrich and Wilhelm Canaris made a lot of attacks on Polish-German frontier. The aim of this provocation incident was to give Hitler argument to attacks on Poland. In September 1939 at the beginning of the Second World War German diversionist agents carried out numerous attacks against the Polish army. Mission of German diversionist agents was also aimed at destruction across the rear of the Polish army, bridges, factories, industry, foundry and coal mines.